Protective Effects of Ophiocordyceps lanpingensis on Glycerol-Induced Acute Renal Failure in Mice - Yanyan Zhang; Yaxi Du; Hong Yu; Yongchun Zhou; Feng Ge (Journal of Immunology Research)
Objective. Oxidative stress and immune response are associated with acute renal failure (ARF). Ophiocordyceps lanpingensis (OL) might be an antioxidant and immunopotentiator. In this study, we explored the protective effects of OL on glycerol-induced ARF. Methods. Male mice were randomly divided into four groups, specifically, glycerol-induced ARF model group, low-dose OL-treated group (1.0 g/kg/d), high-dose OL-treated group (2.0 g/kg/d), and control group. Renal conditions were evaluated using kidney index, serum creatinine (Cr), blood urea nitrogen (BUN), and histological analysis. Rhabdomyolysis was monitored using creatine kinase (CK) level. Oxidative stress was determined using kidney tissue glutathione (GSH), malondialdehyde (MDA), and superoxide dismutase (SOD) levels. Immune status was evaluated using immune organ indices and immunoglobulin G (IgG) level. Results. OL could relieve renal pathological injury and decrease the abnormal levels of kidney index, serum Cr, CK, BUN, and MDA, as well as increase the immune organ indices and the levels of IgG, GSH, and SOD. Treatment with a high dose of OL had more positive therapeutic effects on ARF than using a low dose of OL. Conclusion. OL could ameliorate renal dysfunction in glycerol-induced ARF in mice by inhibiting oxidative stress and enhancing immune response.